Approaches and progress in breeding drought-tolerant maize hybrids for tropical lowlands in west and central Africa - Menkir, A.; Dieng, I.; Gedil, M.; Mengesha Abera, W.; Oyekunle, M.; Riberio, P.F.; Adu, G.B.; Yacoubou, A.M.; Coulibaly, M.; Bankole, F.A.; Derera, J.; Bossey, B.; et al. (Wiley, 2024)
Drought represents a significant production challenge to maize farmers in West and Central Africa, causing substantial economic losses. Breeders at the International Institute of Tropical Agriculture have therefore been developing drought-tolerant maize varieties to attain high grain yields in rainfed maize production zones. The present review provides a historical overview of the approaches used and progress made in developing drought-tolerant hybrids over the years. Breeders made a shift from a wide area testing approach, to the use of managed screening sites, to precisely control the intensity, and timing of drought stress for developing drought-tolerant maize varieties. These sites coupled with the use of molecular markers allowed choosing suitable donors with drought-adaptive alleles for integration into existing elite maize lines to generate new drought-tolerant inbred lines. These elite maize inbred lines have then been used to develop hybrids with enhanced tolerance to drought. Genetic gains estimates were made using performance data of drought-tolerant maize hybrids evaluated in regional trials for 11 years under managed drought stress, well-watered conditions, and across diverse rainfed environments. The results found significant linear annual yield gains of 32.72 kg ha−1 under managed drought stress, 38.29 kg ha−1 under well-watered conditions, and 66.57 kg ha−1 across multiple rainfed field environments. Promising hybrids that deliver high grain yields were also identified for areas affected by drought and variable rainfed growing conditions. The significant genetic correlations found among the three growing conditions highlight the potential to exploit the available genetic resources and modern tools to further enhance tolerance to drought in hybrids.